Lógica fuzzy aplicada à análise de confiabilidade de fundações por estaca hélice contínua - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2019)
Safety is one of the most important aspects for foundations, elements whose function is the transmission to soil of the requests acting on the superstructure of the buildings. Currently, global and partial safety factors are included in the standard, as well as probabilistic reliability studies to verify the safety of foundations. The latter, more efficient than safety factors to verify safety, is a function of the variation of resistance values and demands acting on the structure, and is directly related to the probability of ruin of foundations, an important aspect to be considered in the elaboration of projects. For the case of Continuous Flight Auger piles, currently performed in Brazil and around the world, however, it is known that factors related to the executive process, such as the concrete injection pressure and the drilling speed of the work, can influence the load capacity, on performance, on quality, and therefore on the safety and reliability of piles. Considering this fact, it was proposed in this work the elaboration of a Fuzzy system whose purpose is to obtain a variable that can quantify the reliability of continuous flight auger piles considering design and execution data. The Fuzzy system uses concepts of Fuzzy Logic, 20th century science considered evolution of classical logic and whose main characteristic is the use of vague, imprecise or subjective information for modeling problems. In order to obtain information of this nature related to the piles, an online questionnaire was developed for professionals in the area of Geotechnics, and that served as an aid to the elaboration of the system. The Fuzzy system developed in this work has as input data values related to design and execution parameters of the continuous flight auger piles, and as output data the value of the Fuzzy reliability variable, numerically equal to the probabilistic reliability index, to facilitate the comparison between these values. There was a need to divide the Fuzzy system into two parts. The first, called "previous system", is a Fuzzy system that obtains values of parameters resulting from the insertion of values of the initial parameters, which are the design and execution data of the piles. The second, called "main system", is a Fuzzy system that obtains the Fuzzy reliability variable from the resulting parameters obtained from the previous system. To verify the results of the system, three distinct cases were analyzed based on the Continuous Flight Auger piles project of the University Hospital of the Federal University of Amapá. Then, it was shown the behavior of the graphs for the most unfavorable case analyzed and how these values can be changed for the improvement of the value of the Fuzzy reliability variable. In addition, the probabilistic reliability study of the piles of the University Hospital is carried out for comparison with the values obtained by the Fuzzy system. It was concluded that the Fuzzy system presented satisfactory results for the analyzed cases, although there are aspects to be improved so that it can be used reliably.
Keywords: Lógica fuzzy; Estacas hélice contínua; Fundações profundas; Lógica fuzzy; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA::FUNDACOES E ESCAVACOES; ODS 9 – Indústria, inovação e infraestrutura; ODS 11 – Cidades e comunidades sustentáveis; ODS 12 – Consumo e produção responsáveis